2023
DOI: 10.1002/jeq2.20445
|View full text |Cite
|
Sign up to set email alerts
|

Are service crops an alternative for mitigating N2O emissions in soybean crops in the Argentinian Pampas?

Abstract: Service crops (or cover crops) play an important role in simplified agricultural systems. Service crops reduce agricultural external inputs and increase ecosystem services but their ability to mitigate nitrous oxide (N2O) emissions is still uncertain. The main objective of this study was to evaluate N2O emissions in soybean–soybean (Glycine max [L.] Merr) rotations that included different service crops. Treatments included continuous soybean with winter fallow and soybean with three service crops: oat (Avena s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(112 reference statements)
0
0
0
Order By: Relevance
“…Metaanalyses conducted for the northern hemisphere indicate that legume CCs increase N 2 O emissions compared to other species (Basche et al, 2014;Muhammad et al, 2019). However, studies conducted in the Argentinean Pampas showed no significant differences in N 2 O emissions with or without CCs, including vetch (Vangeli et al, 2022;Petrasek et al, 2023). Regarding NO 3 leaching, lower NO 3 -N content in soil was reported after vetch and other CCs, compared with a fallow condition, suggesting lower potential N losses through this mechanism (Restovich et al, 2012;Frasier et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Metaanalyses conducted for the northern hemisphere indicate that legume CCs increase N 2 O emissions compared to other species (Basche et al, 2014;Muhammad et al, 2019). However, studies conducted in the Argentinean Pampas showed no significant differences in N 2 O emissions with or without CCs, including vetch (Vangeli et al, 2022;Petrasek et al, 2023). Regarding NO 3 leaching, lower NO 3 -N content in soil was reported after vetch and other CCs, compared with a fallow condition, suggesting lower potential N losses through this mechanism (Restovich et al, 2012;Frasier et al, 2017).…”
Section: Discussionmentioning
confidence: 94%